Kemampuan Siswa SMP Dalam Memecahkan Masalah Numerasi Ditinjau Berdasarkan Gender - Khotimah, Khusnul; Siswono, Tatag Yuli Eko (Universitas Negeri Surabaya, 2025)
Problem-solving is a very important part of mathematics learning because, in both the learning process and its application, students have the opportunity to use the knowledge they already possess. One method of problem-solving is using Polya's problem-solving method. At the secondary school level, students consist of both male and female students who inherently have different characteristics and traits. Based on this, a study was conducted with the aim of identifying and describing whether there are differences between male and female junior high school students in solving numeracy problems. This research used a descriptive qualitative method with the subjects being male and female students who have a high level of mathematical ability. The results of the study showed that female students demonstrated a more systematic process in solving numeracy problems, as they were able to write the steps accurately and accompany them with correct results. On the other hand, male students showed a less systematic approach in the problem-solving process, as they tended to skip writing what was known and directly proceeded to the solution steps. Although they sometimes achieved correct results, there were several instances where their answers were inaccurate